Resource Mobilisation and Precarious Workers' Organisations: An Analysis of the Chilean Subcontracted Mineworkers' Unions. (June 2018) - Manky, Omar
Despite the poor working conditions, between 2003 and 2007 Chilean miners organised the longest and largest strikes in the country since the 1980s, obtaining one of the most important recent victories of the Latin American labour movement. This article uses this experience to illustrate the importance of the links between precarious workers and political activists. Drawing on 18 months of extensive fieldwork conducted at several mining sites in Chile, the article contends that the analysis of precarious workers' organisations needs to consider workers' access to different organisational resources, and the role that political parties' militants play in such access, particularly in the Global South.